Food security in South Asia and self-reliance in paddy - Aryal, M; Kandel, M. (Journal of Agriculture and Environment, 2018)
South Asia is world most densely populated region and houses the largest population of undernourished people. It remains the world’s second poorest region with more than 500 million people living on less than US1.25 per day. Firstly this paper attempts to show the general situation and production trend of paddy, secondly, scrutinizes the role paddy has been playing in the economy and food security so far and that it is still the most potential means to improve the food security situation and tackle severe under-nutrition as other sectors are, until now, far less furnished to address this issue. This paper probes into various economic and historical perspectives of rice economy and culture in this region, and shows that self-sufficiency in paddy production is paramount to its domestic food security, and thereby proposes that emphasis should be given on increased rice production which is decelerating amid expansion of modern economic sectors.